Evaluating E-Banking Service Quality and Development Strategies Using the PIESCES and SWOT Frameworks: A Case Study of Commercial Banks in Indonesia - Saripudin (JURNAL ILMIAH EDUNOMIKA, 2026)
The rapid digital transformation of the banking industry has positioned electronic banking (e-banking) as a critical service channel for commercial banks, particularly in emerging economies such as Indonesia. Despite its extensive adoption, challenges related to system reliability, service quality, security, and strategic sustainability remain significant. This study aims to comprehensively evaluate e-banking service quality and to formulate development strategies through an integrated application of the PIESCES framework and SWOT analysis. Employing a qualitative case study approach, data were collected through structured questionnaires, semi-structured interviews, and document analysis involving internal stakeholders responsible for managing e-banking services. The PIESCES framework was utilized to assess six key dimensions of information systems performance: performance, information, economy, control, efficiency, and service. Subsequently, SWOT analysis was applied to translate service quality evaluation outcomes into strategic development directions by identifying internal strengths and weaknesses alongside external opportunities and threats. The findings indicate that e-banking services significantly enhance transaction efficiency and accessibility; however, persistent issues related to system stability, cybersecurity control, and responsiveness of supporting services require strategic attention. The integration of PIESCES and SWOT provides a robust analytical foundation for aligning service quality evaluation with strategic planning. This study contributes to the literature by offering an integrative evaluation–strategy model for digital banking services and provides practical implications for bank management in strengthening competitiveness and ensuring sustainable e-banking development.